The Stabilizing Effect of Multimedia on ESL Spelling Retention: A Mixed-Methods Study - Pandayan, Rhio (Journal of Education and Learning Reviews, 2025)
Background and Aim: This research was conducted to stabilize the spelling retention of English as a Secondary Language (ESL) learners through a multimedia intervention combining weekly short videos that featured vocabulary spelling, pronunciation, definitions, and photos. This, with notebook writing and teacher-guided practice among grade 5 students. Materials and Methods: The Action research paradigm guided the implementation of the intervention, encompassing planning, implementation, observation of outcomes, and reflection on results. Using an explanatory sequential design, quantitative data from 20 weeks of spelling scores from weekly assessments were analyzed and then explained further by the qualitative data from student focus groups, interviews, and teacher observation. Results: Quantitatively, students' spelling performance remained stable with an average score of 7.40 out of 10 (SD = 0.68). Minimally, scores fluctuated, which indicates consistent retention rather than progressive improvement. The stable scores suggest that while the multimedia intervention maintained prior knowledge, additional strategies may be required to foster further improvement. The qualitative themes are varying engagement patterns, different multimedia design preferences, mixed perceived efficacy and learning outcomes, support systems, and content relevance and accessibility. Conclusion: Multimedia interventions effectively stabilized spelling retention in ESL learners but did not indicate improved performance. This implies that there is a necessity for better optimization of multimedia with the Cognitive Theory of Multimedia Learning (CTML) by syncing text and visuals, reducing text density, and segmenting videos. Support for academically struggling students and exploring engagement strategies should be increased. More implications are for consistently using themed units for relevance, gamification for heightened motivation, and training educators on CTML and hybrid learning methods for proper and consistent application of the intervention. The connection between independent practice and guided support proved crucial to stabilizing the student performance.